2013
DOI: 10.1016/j.wem.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Emergency Medical Services Events in US National Parks From 2007 to 2011

Abstract: On a national level, the NPS experiences an equal number of medical and traumatic EMS events. This differs from past observed trends that reported a higher incidence of traumatic events than medical events in wilderness settings. Cardiac events and automated external defibrillator usage are relatively infrequent. Traumatic fatalities are more common than medical fatalities in the NPS. Regional variations in events likely reflect differences in terrain, common activities, proximity to urban areas, and access to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…7 Other previously published injury/illness event rates per 100,000 visitors included 4.7 at Mount Rainier National Park, 1.27 at Olympic National Park, and 2.7 at Shenandoah National Park. 7,16,18 As described, APIS is a smaller, remotely located park, attracting mostly local visitors year-round. Recreation at APIS often involves unpredictable weather patterns, frequent storms, and risk of inclement weather.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Other previously published injury/illness event rates per 100,000 visitors included 4.7 at Mount Rainier National Park, 1.27 at Olympic National Park, and 2.7 at Shenandoah National Park. 7,16,18 As described, APIS is a smaller, remotely located park, attracting mostly local visitors year-round. Recreation at APIS often involves unpredictable weather patterns, frequent storms, and risk of inclement weather.…”
Section: Discussionmentioning
confidence: 99%
“…12 From 2008 to 2012, Isle Royale reported 270 total injuries/illnesses and 77,039 total visitors, yielding a calculated injury/illness rate of 350 injury/illness events per 100,000 visitors, which is markedly higher than any of the previously reported rates in the literature. 7,12,16,18,27 It is difficult to explain these differences because of the limited information regarding the authors' inclusion criteria, and thus a comparison to Isle Royale is limited by these constraints. 12 More broadly, an exploration of injury/illness rates reported at other parks (and national averages) provides insight into the relative hazardousness of APIS.…”
Section: Discussionmentioning
confidence: 99%
“…Data from search and rescue services can be a valuable source of information on accidents during various outdoor sports and recreation. The incidence of events requiring emergency medical services in US National Parks is 45.9 events per 1 million visitors, with almost equal percentage due to traumatic and medical conditions . Hypothermia as well as fatigue/exhaustion are among the most common illnesses reported in some of the most northern US parks .…”
Section: Epidemiology: Estimating Incidence and Mortality Of Accidentmentioning
confidence: 99%
“…The incidence of events requiring emergency medical services in US National Parks is 45.9 events per 1 million visitors, with almost equal percentage due to traumatic and medical conditions. 57 Hypothermia as well as fatigue/exhaustion are among the most common illnesses reported in some of the most northern US parks. 58,59 Data from mountain rescue teams in Scotland over a two-year period (January 1998-December 1999) showed that 3.5% (2/57) of fatalities were due to hypothermia and 13.8% (46/333) of all non-fatality incidents were persons suffering from cold or exhaustion without other injuries or illnesses.…”
Section: Data Based On Search and Rescue Activitiesmentioning
confidence: 99%
See 1 more Smart Citation